2022
DOI: 10.2337/dc21-2048
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Fatty Acids and Genetic Predisposition to Type 2 Diabetes: Gene-Nutrient Interaction Analysis

Abstract: OBJECTIVE To assess the relationship of circulating fatty acids (FA) with risk of type 2 diabetes (T2D) and potential interactions with genetic risk. RESEARCH DESIGN AND METHODS A total of 95,854 participants with complete data on plasma FA from the UK Biobank were enrolled between 2006 and 2010 and were followed up to the end of 2020. Plasma concentrations of saturated FA (SFA), monounsaturated FA (MUFA), and polyunsaturated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Our study indicated a negative correlation between PUFA/SFA and PUFA/MUFA ratios with T2DM. A study exploring complete data on plasma fatty acids from 95,854 participants in the UK Biobank between 2006 and 2010 revealed a positive association of SFA (OR: 1.03) and MUFA (OR: 1.03) with T2DM, while PUFA (OR: 0.62) showed a negative association with T2DM [ 44 ]. Substituting dietary SFA with PUFA improved insulin sensitivity within just 5 weeks, thereby decreasing the risk of developing T2DM [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study indicated a negative correlation between PUFA/SFA and PUFA/MUFA ratios with T2DM. A study exploring complete data on plasma fatty acids from 95,854 participants in the UK Biobank between 2006 and 2010 revealed a positive association of SFA (OR: 1.03) and MUFA (OR: 1.03) with T2DM, while PUFA (OR: 0.62) showed a negative association with T2DM [ 44 ]. Substituting dietary SFA with PUFA improved insulin sensitivity within just 5 weeks, thereby decreasing the risk of developing T2DM [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study of 11 offspring of obese and T2DM patients indicated that weight maintenance with a MUFA-rich diet improved homeostasis model assessment of insulin resistance and fasting pro-insulin levels in insulin-resistant subjects (28). Zhuang et al also conducted a follow-up study and found that plasma concentrations of MUFA were positively associated with T2DM risk (29). Notably, studies of MUFA and diabetes risk are limited and controversial.…”
Section: Figurementioning
confidence: 99%
“…Mean age of participants in the individual studies ranged from 41.1 to 80.5 years. For the measurements of omega-3 PUFA levels, 51 studies used GC analytic approach [16e18,32,34e41,43e54,57e59,61e64,66e70,73e79,81, 83,85,87e90,92], 13 used GLC [31,33,43,55,56,65,71,72,80,82,84,86,91], one in nuclear magnetic resonance-based profiling [42], and one used GCetandem mass spectrometry [60]. Fig.…”
Section: Study Characteristicsmentioning
confidence: 99%